Introduction, Connection, Application, Reflection, Extension-Multimedia Based Integrated Instruction (ICARE-U): A Model to Improve Creative Thinking Skills - Pratiwi, Mala; Samsudin, Achmad; Aminudin, Adam Hadiana; Aminudin, Adam Hadiana; Rais, Abdul; asmitadila, R; Rachmadtullah, Reza (International Journal of Psychosocial Rehabilitation, 2020)
The study is aimed to improve students’ creative thinking skills as the impact of the implementation of Introduction, Connection, Application, Reflection, Extension-Multimedia Based Integrated Instruction (ICARE-U). The method that has been used in this research is the 3D+1I model which has four comprehensive steps are Defining, Designing, Developing, and Implementing. The participants of this research are eleven grade students who come from Bandar Lampung (13-man namely “Mekhanai”, and 17-women namely “Muli”). The data was obtained from the respondents through pre-test and post-test in order to quantify the effects on the students’ creative thinking skills. The results of this study present that the ICARE-U model generally effected the students’ creative thinking skills. Furthermore, the score of N-Gain indicates that students’ creative thinking skills are affected by the average score of 0.7 characterized as the medium. In addition, trough the scalogram as a product of Rasch analysis, it can be concluded that “Muli” has a greater value than “Mekhanai”. This is affected by the implementation of ICARE with the MBI2 (ICARE-U) model to the presentation step.